CircRNA CDR1as knockdown inhibits progression of non‐small‐cell lung cancer by regulating miR‐219a‐5p/SOX5 axis. Issue 3 (9th January 2020) - Li, Yaming; Zhang, Jinzhao; Pan, Shuang; Zhou, Jing; Diao, Xin; Liu, Song
Abstract : Background: Circular RNAs (circRNAs) participate in the development of human cancers by regulating multiple cell processes. CircRNA antisense to the cerebellar degeneration‐related protein 1 transcript (circCDR1as) expression is dysregulated in many cancers, including non‐small‐cell lung cancer (NSCLC). However, the mechanism by which circCDR1as mediates the development of NSCLC remains unknown. Methods: A total of 30 paired cancer and normal tissues were collected from patients with NSCLC. The expression levels of circCDR1as, microRNA (miR)‐219a‐5p and Sex determining region Y‐box protein 5 (SOX5) were measured in tissues or cells by quantitative real‐time polymerase chain reaction or western blot. Cell viability, apoptosis, migration and invasion were detected by 3‐(4, 5‐dimethylthiazol‐2‐yl)‐2, 5‐diphenyl‐tetrazolium bromide, colony formation, flow cytometry and transwell assays, respectively. The target relationship between miR‐219a‐5p and circCDR1as or SOX5 was validated by dual‐luciferase reporter assay. Results: CircCDR1as expression was elevated in NSCLC tissues and cells in comparison to the matched controls. Interference of circCDR1as led to obvious inhibition of cell viability, migration and invasion and increase of apoptosis in NSCLC cells. MiR‐219a‐5p acted as a target of circCDR1as and miR‐219a‐5p downregulation attenuated the regulatory effect of circCDR1as silencing on NSCLC progression. Moreover, miR‐219a‐5p targeted SOX5 to repress the progression of NSCLC in vitro. Besides, circCDR1as knockdown reduced the expression of SOX5 by increasing miR‐219a‐5p level. Conclusion: Knockdown of circCDR1as inhibited the progression of NSCLC by decreasing cell viability, migration and invasion and increasing apoptosis by upregulating miR‐219a‐5p and downregulating SOX5.